Gastric metaplasia and duodenal ulcer disease in children infected by Helicobacter pylori. Issue 4 (April 1996) - Gormally, S M; Kierce, B M; Daly, L E; Bourke, B; Carroll, R; Durnin, M T; Drumm, B
Abstract : BACKGROUND--Helicobacter pylori infection of the gastric mucosa is vital in the pathogenesis of duodenal ulcer disease. H pylori will only colonise gastric epithelium and its association with duodenal disease is therefore not easily explained. AIMS--To determine if gastric metaplasia in the duodenum increases the risk of duodenal ulcer disease in children infected with H pylori. PATIENTS--All children undergoing upper endoscopy over a 20 month period in a children's hospital in Ireland. METHODS--Two biopsy specimens were obtained from the antral mucosa and two from the first part of the duodenum. One antral biopsy specimen was used in a rapid urease test (Clo Test). Biopsy sections were stained with haematoxylin and eosin and also with cresyl violet for identification of H pylori. Periodic acid Schiff (PAS) stain was performed to identify areas of gastric metaplasia. RESULTS--Gastric and duodenal biopsy specimens were obtained from 148 patients (M:F 1:2:1). Twenty five children (17%) had H pylori positive gastritis. Thirty four children (23%) had gastric metaplasia in the duodenum. Nine per cent of children under the age of 8 years had gastric metaplasia compared with 38% in those 12 years of age or over (p < 0.005). Seven children had duodenal ulcer disease. Gastric metaplasia was present in six of seven (86%) children with duodenal ulcer disease compared with 28 of 141 (20%) without ulceration (p < 0.001). While both H pylori and gastric metaplasia were each significant risk factors for duodenal ulcer disease, the combined presence of both factors was associated with a pronounced increase in duodenal ulcer disease. Duodenal ulcer disease occurred in over 50% of children with both H pylori infection and gastric metaplasia. In contrast duodenal disease did not occur in children (0 of 100) when both were absent. CONCLUSION--The presence of gastric metaplasia in the duodenum is the major risk factor for duodenal ulcer disease in patients colonised by H pylori.